2013
DOI: 10.1186/1756-6606-6-59
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sleep disorders under pain using an optogenetic tool: possible involvement of the activation of dorsal raphe nucleus-serotonergic neurons

Abstract: BackgroundSeveral etiological reports have shown that chronic pain significantly interferes with sleep. Inadequate sleep due to chronic pain may contribute to the stressful negative consequences of living with pain. However, the neurophysiological mechanism by which chronic pain affects sleep-arousal patterns is as yet unknown. Although serotonin (5-HT) was proposed to be responsible for sleep regulation, whether the activity of 5-HTergic neurons in the dorsal raphe nucleus (DRN) is affected by chronic pain ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 54 publications
3
66
0
Order By: Relevance
“…It has been reported that both ␣ and ␤ receptors are distributed in the PFC [15,16]. Although further studies are needed using an optogenetic tool with TH-cre transgenic mice in which AAV-HAL (a light-driven chloride pump) is injected into the LC, we propose that the acceleration of LC-PFC noradrenergic neurons, as well as DRN-5-HTergic neurons [5] may, at least in part, explain the sleep disturbance under a state of neuropathic pain.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…It has been reported that both ␣ and ␤ receptors are distributed in the PFC [15,16]. Although further studies are needed using an optogenetic tool with TH-cre transgenic mice in which AAV-HAL (a light-driven chloride pump) is injected into the LC, we propose that the acceleration of LC-PFC noradrenergic neurons, as well as DRN-5-HTergic neurons [5] may, at least in part, explain the sleep disturbance under a state of neuropathic pain.…”
Section: Discussionmentioning
confidence: 84%
“…In a previous study, we found that sciatic nerve-ligated mice exhibited sleep disturbance along with thermal hyperalgesia [5]. Although it has been considered that several areas in the brainstem and forebrain are important for modulation and expression of the sleep/wake cycle [8], and several neurotransmitters and neuropeptides are involved in modulation of this cycle [9][10][11], the neurophysiological and molecular mechanisms by which neuropathic pain affects sleep/arousal patterns are not fully understood.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Serotonin (5-HT) neurons located in the rostral brain stem comprise a component of the ascending arousal system that is responsible for regulating sleep-wake transitions (Brown et al 2012;Ito et al 2013). 5-HT neurons, including those in this region, are chemosensitive (Richerson 2004;Severson et al 2003).…”
mentioning
confidence: 99%
“…Manipulation of the targeted neurons in the spinal cord and hindbrain showed that glutamatergic neurons in the spinal cord are critical for generating rhythm in the central pattern generators and the activation of glutamatergic reticulospinal neurons in hindbrain area is sufficient to activate directly the spinal locomotor network [18]. Likewise, the promoter regions of vesicular GABA transporter, choline acetyltransferase or tryptophan hydroxylase 2 have been used to target GABAergic, cholinergic, or serotonergic neurons, respectively [19,[24][25][26][27].…”
Section: Genetic Identitymentioning
confidence: 99%